Application of a single‐colony coculture technique to the isolation of hitherto unculturable gut bacteria. (February 2015) - Tanaka, Yoshiki; Benno, Yoshimi
ABSTRACT Molecular studies have led to postulation of a relationship between gut microbiota and certain diseases. However, because studies of hitherto uncultured species in vivo are essential for characterizing the biology and pathogenic properties of gut bacteria, techniques for culturing and isolating such bacteria must be developed. Here, a technique is described that partially overcomes the obstacles that prevent detection of interbacterial communication in vitro and are thus responsible for the failure to culture certain bacterial species. For this purpose, a ring with a membrane filter at the bottom was designed and a relatively simple nutrient medium was used instead of conventional media. Gut bacteria were cocultivated in soft agar separated by the membrane filter to simulate interbacterial communication in vitro. Use of this soft agar coculture technique led to the successful isolation of hitherto uncultured bacteria and the demonstration of multistage interbacterial communication among gut bacteria in vitro. Cultivation and isolation of single colonies of bacteria that require other bacteria for growth will enhance efforts to better understand the physiological and pathogenic roles of gut microbiota.